HUBUNGAN PENGGUNAAN OBAT HERBAL (JAMU GEPYOK) DENGAN PRODUKSI ASI DI BPS DS. NGUMPAKDALEM KEC. DANDER KABUPATEN BOJONEGORO TAHUN 2017 - Fitria Rizky Kurniawati (Jurnal Ilmiah Kesehatan, 2019)
Abstract Indonesian society's interest in complementary or traditional therapy is increasing. The frequency of utilization of complementary alternative therapies is increasing rapidly throughout the world. The result of Susenas (2007) shows Indonesians who complain of pain within the month before the 30.90% survey. Of the residents who complained of illness, the largest percentage (65.01%) chose their own treatment using traditional medicines and / or drugs. The use of traditional medicine in self-medication efforts has steadily increased from 15.2% to 38.3% over the course of 7 years from 2000-2006 (Supardi, S and Andi Leny, 2010) The purpose of this study is to determine the effect of the use of herbal medicine to facilitate the expansion of breast milk as an effort to reduce the use of conventional medicines in Bojonegoro District in 2017. This research uses Quasy experimental research design technique (quasi experiment). Based on the place of study including the type of field research design. Population is a subject that meets the criteria that have been set. The population in this study were all breastfeeding mothers in 10 Puskesmas in Bojonegoro Regency in 2016. Analysis is a very important part to achieve the goal, where the main purpose of research is to answer the research questions in expressing the phenomenon . Data analysis in this study using chi square test. The results showed p value 0.468> 0.05 which means there is no relationship between the use of herbal uyup - uyup with milk production. Keywords: Herbal Medicinal Use and Breastmilk Production